GENERATION Z AND CULTURAL SENSITIVITY: INTEGRATING CROSS-CULTURAL UNDERSTANDING INTO TODAY'S EDUCATIONAL CURRICULUM - Hidayah Tullah. S, Nur; Rosa Mistika Sato, Maria; Annisa Suci, Nur; Sahib, Nurfaizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Generation Z, having grown up in the digital era, is highly exposed to global cultural diversity but does not necessarily possess adequate intercultural competence. This study critically examines how cross-cultural understanding can be effectively integrated into contemporary educational curricula, taking into account the unique characteristics of Generation Z as learners. The research employs a Systematic Literature Review (SLR) method combined with comparative policy analysis, drawing on scholarly sources published between 2022 and 2026. Data were analyzed using inductive thematic analysis, yielding four main themes: (1) the cross-cultural characteristics and needs of Generation Z, (2) the implementation of culturally sensitive curricula, (3) the role of digital technology as a mediator of intercultural competence, and (4) a comparative analysis of multicultural education models across countries. Findings reveal that most existing curricula remain additive in nature and have yet to respond transformatively to the needs of Generation Z. Digital technology plays a paradoxical role expanding cultural exposure while simultaneously creating filter bubbles making the integration of digital and cultural literacy critically important. The experiences of Finland, Singapore, and the United States demonstrate that effective multicultural education models are transformative-structural in nature and supported by sustained professional development for teachers. Indonesia, with its 714 ethnic groups and more than 700 regional languages, holds tremendous potential to develop a locally grounded model of cross-cultural education. This study recommends transformative curriculum reform, enhanced teacher pedagogical competence, and the synergistic integration of digital and cultural literacy to prepare Generation Z as empathetic and culturally competent global citizens.